ChemInform Abstract: Multicomponent Synthesis of Functionalized Tetrahydroacridinones: Insights into a Mechanistic Route. Issue 12 (March 2016) - Chung, Tsai‐Wen; Narhe, Bharat D.; Lin, Chun‐Cheng; Sun, Chung‐Ming
Abstract: As part of a mechanistic study of 3‐component reactions between aldehydes, 1, 3‐diones and aromatic amines, initially prepared Michael adducts (I) are reacted with arylamines giving the title compounds in good to high yields and remarkable differences in regioselectivity during annulation between O‐ and N‐heterocycles (II) and (IV).